Study of fuzzy and PI controller for permanent-magnet brushless DC motor drive - Tan, Chee Siong; Baharuddin, Ismail; Mohd Fayzul, Mohammed; Mohd Faridun Naim, Tajuddin; Siti Rafidah, Abd. Rahim; Zainuddin, Mat Isa (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/